EVALUATION OF CATARACT PREVENTIVE ACTION OF PHYCOCYANIN (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Phycocyanin is a biliprotein pigment found in blue-green algae Spirulina platensis, which have attracted attention because of their nutritional value and medicinal properties. This pigment has antioxidant, anti-inflammatory and hepatoprotective activity in different experimental models. This data supports the view that phycocyanin may prevent cataract progression. Cataract preventive action of phycocyanin was evaluated against naphthalene and galactose induced cataract experimental models in wistar rats at dose 200 mg/kg/day p.o and vitamin E was used as a reference standard. Phycocyanin treated animals showed no opacification in the lens and they also showed significantly increased level of glutathione (GSH), soluble proteins and water content as compared to positive control group in the lens in both the experimental models. Cataract preventive action of phycocyanin may be due to is antioxidant and free radical scavenging activity.